2014
DOI: 10.1016/j.jad.2014.04.068
|View full text |Cite
|
Sign up to set email alerts
|

Association of testosterone levels and future suicide attempts in females with bipolar disorder

Abstract: Background Considerable evidence suggests that testosterone may play a role in the pathophysiology of mood disorders in females. This is the first prospective study to examine whether blood testosterone levels predict suicide attempts in females with bipolar disorder. Methods Females with a DSM-IV diagnosis of a bipolar disorder in a depressive or mixed episode with at least one past suicide attempt were enrolled. Demographic and clinical parameters were assessed and recorded. Plasma testosterone was assayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 49 publications
(70 reference statements)
0
34
0
Order By: Relevance
“…In the current study, higher neighborhood SES in puberty was also related to lower adulthood levels of FAI (albeit in the follow-up analyses only), and FAI is an established risk factor for cardiovascular risk. Although, to our knowledge, no studies having examined early life adversity exposures in relation to androgens directly, correlates of early life adversity (i.e., depressive symptomatology) have been associated with androgen excess (Sher et al, 2014; Vogel, Klaiber, & Broverman, 1978). …”
Section: Discussionmentioning
confidence: 99%
“…In the current study, higher neighborhood SES in puberty was also related to lower adulthood levels of FAI (albeit in the follow-up analyses only), and FAI is an established risk factor for cardiovascular risk. Although, to our knowledge, no studies having examined early life adversity exposures in relation to androgens directly, correlates of early life adversity (i.e., depressive symptomatology) have been associated with androgen excess (Sher et al, 2014; Vogel, Klaiber, & Broverman, 1978). …”
Section: Discussionmentioning
confidence: 99%
“…Possibly, higher levels of lithium in the drinking water decrease suicide rates among men by reducing impulsivity and aggression (Sher, 2015). Another possible hypothesis is related to a potential role of testosterone in suicidal behavior because higher testosterone levels were associated with higher suicidality (Sher et al, 2012(Sher et al, , 2014 and testosterone levels are much higher in men than in women (Shahidi, 2001). The administration of lithium has been reported to reduce testosterone levels (Thakur et al, 2003;Ghosh et al, 1991) and it is interesting to speculate that lithium reduces suicidality in men by decreasing testosterone levels (Sher, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, low testosterone levels are associated with suicidal behaviour in older men while high testosterone levels are related to suicidal behaviour in adolescents and young adults. It is of interest to note that one of our studies has shown that blood testosterone levels may be associated with suicidal behaviour in women (10). We have observed that higher baseline testosterone levels predicted suicide attempts during the follow-up period up to 2.5 years in women with bipolar disorder.…”
mentioning
confidence: 54%